2016
DOI: 10.1186/s12967-016-1014-6
|View full text |Cite
|
Sign up to set email alerts
|

Methylation pattern analysis in prostate cancer tissue: identification of biomarkers using an MS-MLPA approach

Abstract: BackgroundEpigenetic silencing mediated by CpG island methylation is a common feature of many cancers. Characterizing aberrant DNA methylation changes associated with prostate carcinogenesis could potentially identify a tumour-specific methylation pattern, facilitating the early diagnosis of prostate cancer. The objective of the study was to assess the methylation status of 40 tumour suppressor genes in prostate cancer and healthy prostatic tissues.MethodsWe used methylation specific-multiplex ligation probe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Park et al [24] concluded that the CpG island methylation of the SCGB3A1 gene is an early event that predominantly occurs during the preinvasive stage of breast cancer and accumulates with breast cancer progression. Moreover, Gurioli et al [25] reported that the SCGB3A1 methylation levels gradually increased from low and intermediate in healthy noncancerous tissue to high in cancerous tissue. Another study demonstrated that a three-gene panel including the SCGB3A1 gene could distinguish between breast ductal carcinoma in situ and normal breast tissues with 96% sensitivity and 87% specificity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [24] concluded that the CpG island methylation of the SCGB3A1 gene is an early event that predominantly occurs during the preinvasive stage of breast cancer and accumulates with breast cancer progression. Moreover, Gurioli et al [25] reported that the SCGB3A1 methylation levels gradually increased from low and intermediate in healthy noncancerous tissue to high in cancerous tissue. Another study demonstrated that a three-gene panel including the SCGB3A1 gene could distinguish between breast ductal carcinoma in situ and normal breast tissues with 96% sensitivity and 87% specificity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty studies were published between 2002 and 2018 and included 1640 prostate cancer patients and 769 controls. Eight studies were conducted in Europe, [19][20][21][22][23][24][25][26] six studies were conducted in Asia, [27][28][29][30][31][32] and six studies were conducted in North America. [33][34][35][36][37][38] The quality assessment results of the included studies showed that the included studies had high quality and could be used for meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…CpG methylation of the 5’ region of the RAR β gene contributes to gene silencing, and this methylation is associated with increased grades of SIL and invasive cervical cancer. Many studies have revealed that methylation of CpG islands in the promoter region of the RAR β gene induces repression of RAR β expression in several epithelial carcinomas, including cervical cancer[ 53 - 55 ].…”
Section: Epigenetic Mechanisms and Risk Of Cancer Developmentmentioning
confidence: 99%